2015
DOI: 10.4103/2348-0548.165055
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function monitoring

Abstract: Neuro-cognitive dysfunction quite frequently occurs after major surgery particularly in elderly patients. Cognitive function monitoring becomes an important tool in the perioperative period, especially for patients undergoing neurosurgical procedures as these patients are at a greater risk because of the nature of surgery. Many cognitive assessment tools were described, but selecting a tool or combination of tools to assess depends on preoperative patient condition, availability of informant and post-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…WM is a system that protects and manages information temporarily during the planning and execution of many cognitive tasks, and an active WM is required for all occupational performance areas, from the completion of dressing without reminder to the ability to do their homework independently (Kulkarni and Moningi, 2015; Nouchi and Kawashima, 2014). In this study, most families’ “true” or “definitely true” answers to statements such as “Has difficulty remembering what he/she is doing, in the middle of an activity” and “When asked to do several things, he/she only remembers the first or last” may express the influence of WM on children with MB.…”
Section: Discussionmentioning
confidence: 99%
“…WM is a system that protects and manages information temporarily during the planning and execution of many cognitive tasks, and an active WM is required for all occupational performance areas, from the completion of dressing without reminder to the ability to do their homework independently (Kulkarni and Moningi, 2015; Nouchi and Kawashima, 2014). In this study, most families’ “true” or “definitely true” answers to statements such as “Has difficulty remembering what he/she is doing, in the middle of an activity” and “When asked to do several things, he/she only remembers the first or last” may express the influence of WM on children with MB.…”
Section: Discussionmentioning
confidence: 99%
“…Combined or multimodal exercise interventions that include a motor component (movement speed, balance, motor coordination and flexibility) have also been shown to improve cognitive function in older adults (VoelckerRehage et al 2010). Although questions still remain as to the optimal type and dose of exercise that is most effective to improve cognitive function in older adults, a meta-analysis of single or bimodal exercise trials indicated a small-to-moderate effect on cognitive performance with combined aerobic and PRT compared to aerobic training alone in older adults (Colcombe & Kramer 2003 Kulkarni & Moningi (2015) and McGinty et al (2014). D-KEFS, Delis-Kaplan executive function system; WAIS-R, Wechsler adult intelligence scale-revised; WAIS-III, Wechsler adult intelligence scale-third edition; WMS-R, Wechsler memory scales-re-vised edition; WMS-III, Wechsler memory scales-third edition.…”
Section: Effects Of Exercise Training On Cognitive Function In Men Onmentioning
confidence: 99%